WeChat is a Communication Platform in The Logistics Business Between Indonesia and China - Sopianti, Eva; Francisca Sestri Goestjahjanti; Winanti; Istajib Kulla Himmy’azz; Dedi Sopyan (International Journal of Innovation Research in Education, Technology and Management, 2025)
The globalization of trade between Indonesia and China has significantly increased the demand for logistics. With the role of technology, business communication has become more effective and efficient. WeChat has become an essential digital communication platform in logistics, particularly in export and import activities between Indonesia and China. This study examines the role of WeChat as a communication platform in the logistics industry, focusing on its features and impact on business efficiency and cross-border collaboration. The findings reveal that WeChat facilitates real-time communication, simplifies document sharing, and enhances operational coordination. Challenges such as data privacy and platform dependence are also discussed. This study contributes to understanding the digital transformation of logistics through social media platforms in Southeast Asia